Nonanuclear zinc–gold [Zn3Au6] heterobimetallic complexes. Issue 24 (2nd June 2021) - Yadav, Ravi; Dahlen, Milena; Singh, Akhil K.; Sun, Xiaofei; Gamer, Michael T.; Roesky, Peter W.
Abstract : Heterobimetallic nonanuclear Zn–Au complexes are synthesized. The complexes comprise a trinuclear Zn core and six Au(i ) moieties on the periphery. Photoluminescence of the Zn-metalloligand and the Zn–Au complex has also been studied. Abstract : Nonanuclear zinc–gold heterobimetallic complexes were synthesized in a two-step process. Commercially available carboxy-functionalized phosphine ligands were used for selective binding to Zn and Au centers. In the first step, bipyridine coordinated Zn-metalloligands with free phosphine moieties were prepared. Reaction of Zn-metalloligands with [AuCl(tht)] (tht = tetrahydrothiophene) resulted in the formation of nonanuclear Zn–Au heterobimetallic complexes. The flexibility of the carboxy-functionalized phosphine ligands was shown to be crucial for the formation of aurophilic interactions. Further, the photoluminescence of the Zn-metalloligands and one Zn–Au complex was investigated at room temperature as well as 77 K. The emission spectra showed clear difference between the Zn-metalloligands and the Zn–Au complex.